House Season 7 Disc 1 - Edelstein, Lisa, 1967-; Wilde, Olivia; Epps, Omar.; Laurie, Hugh, 1959-; Leonard, Robert Sean, 1969-; Universal Studios, Inc.; Universal Studios Home Entertainment (Firm) (Universal City, CA : Universal Studios Home Entertainment, 2011)
He's sarcastic, incorrigible, bitter, and in a relationship? Dr. Gregory House has spent his career taking on seemingly hopeless cases, but when his rapport with Dr. Lisa Cuddy changes, he finds himself facing new, and very different, challenges. His team at Princeton-Plainsboro Teaching Hospital also continues to blaze trails as they investigate baffling medical cases involving a religious zealot, a professional bull rider, and possibly even smallpox.
Now what? -- Selfish -- Unwritten -- Massage therapy -- Unplanned parenthood.
Videodisc release of the 2010 television series broadcast.
Title from disc label.
Anamorphic widescreen presentation.
Bonus features: trailers and previews.
Lisa Edelstein, Olivia Wilde, Omar Epps, Robert Sean Leonard, Hugh Laurie.
Not rated.
Keywords: Physician and patient -- United States -- Drama; Hospitals -- Medical staff -- United States -- Drama; Hospital patients -- United States -- Drama; United States; Drama; Fiction television programs; Medical television programs; Television series; Video recordings for the hearing impaired